Pedagogical technology of forming the linguistic competence of future teacher of primary school - Мамчич, Олена; Калініна, Ірина (Pedagogy of Higher and Secondary Education, 2014)
Mamchich О. В., Kalinina I. Р. Pedagogical technology of forming the linguistic competence of future teacher of primary school. The article is devoted to the research of forming of linguistic competence of future elementary school teachers in pedagogical higher schools. The pedagogical conditions of forming linguistic competence, the system of forming includes the forming methods, the theoretical and practical complex of subjects and tasks.